Conduction mechanisms on high retention annealed mgo-based resistive switching memory devices - Loy, Desmond Jia Jun (2019)
We report on the conduction mechanisms of novel Ru/MgO/Cu and Ru/MgO/Ta resistive switching memory (RSM) devices. Current-voltage (I–V) measurements revealed Schottky emission (SE) as the dominant conduction mechanism in the high resistance state (HRS), which was validated by varying temperatures and transmission electron microscopy (TEM) results. Retention of more than 10 years at 85 °C was obtained for both Ru/MgO/Ta and Ru/MgO/Cu RSM devices. In addition, annealing processes greatly improved the consistency of HRS and LRS switching paths from cycle to cycle, exhibiting an average ON/OFF ratio of 102. Further TEM studies also highlighted the difference in crystallinity between different materials in Ru/MgO/Cu RSM devices, confirming Cu filament identification which was found to be 10 nm in width.